PREDIKSI CURAH HUJAN BULANAN DI DELI SERDANG MENGGUNAKAN PERSAMAAN REGRESI DENGAN PREDIKTOR DATA SUHU DAN KELEMBAPAN UDARA - Saragih, Immanuel Jhonson Arizona; Inlim Rumahorbo; Ricko Yudistira; Dedi Sucahyono (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2020)
A simulation of monthly rainfall prediction (RR) using a regression equation with a predictor of air temperature (T) and humidity (RH) has been tried at Deli Serdang Climatology Station, North Sumatra. The RR, T and RH data for 30 years (1989-2018) were obtained from the Deli Serdang Climatology Station. This prediction simulation for total monthly rainfall uses simple linear regression and multiple linear regression. Evaluation is done by comparing and calculating the Pearson correlation value and the deviation of the predicted total monthly rainfall against the actual total rainfall. The results of data processing showed that the simulation of the total monthly rainfall forecast for 2019 in the Deli Serdang area obtained a correlation value of r = 0,72 and an average of RMSE = 77,42 mm / month using air temperature predictors, obtained correlation values r = 0,73 and RMSE = 77,13 mm / month using the air humidity predictor, and the correlation value r = 0,70 with RMSE = 80,53 mm / month using a predictor of air temperature and air humidity as well.